IMPROVING WORK ENGAGEMENT OF GAS STATION OPERATOR WITH THE ROLE OF JOB RESOURCE, JOB DEMAND, AND JOB SATISFACTION - Syailendra, Bianca; Soetjipto, Budi W. (Universitas Brawijaya, Indonesia, 2017)
Gas station operator is the spearheading of organizations that deal directly with the public because the operator must have work engagement in order to carry out the work in accordance with the company's expectations. The purpose of this study is to determine the effect of job demand, job resources, and job satisfaction at gas station operator to work engagement. The study involved 200 operators at a gas station in Jakarta with a quantitative method. The result is job demand positive and significant impact on job satisfaction, job satisfaction positive and significant impact on the work engagement, job resource influential slight positive but not significant to work engagement, job demand positive effect but not significant to work engagement, and job resource negative and not significant effect on job satisfaction. The study found the results that the effect of job demand in gas station operator is in contrast with previous studies and the effect of job resource is also different in previous studies because of differences in the job demand and level of job satisfaction.